PELATIHAN BUKU BESAR DI SMA NEGERI 2 JAKARTA - Theresia, Friska; Adang, Ferry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The Ledger Training at SMA Negeri 2 Jakarta is structured to provide opportunities for students who are interested in education to act as teacher assistants at school. This training aims to increase students' understanding of the concepts and skills related to ledgers in the field of accounting. The teaching assistance program was implemented at State High School 2 Jakarta from 14 August 2023 to 3 November 2023. SMA Negeri 2 Jakarta is a superior state high school located in Taman Sari, West Jakarta. This research uses a cooperative approach in the form of discussion and analysis of student responses to evaluate the effectiveness of assistance in designing interesting and meaningful learning. In cooperative teaching methods, students work together in groups to achieve learning goals. By using cooperative methods, students can learn to work together, share ideas, and overcome challenges together. The results of Teaching Assistance at SMA Negeri 2 Jakarta can be seen in the increase in interpersonal skills and self-confidence of SMA Negeri 2 Jakarta students. The process of interacting with teaching assistants can improve students' communication, collaboration and problem-solving skills. In this way, the MBKM program not only has an impact on students' academic achievement, but also forms individuals who are better prepared to face challenges in the world of education and careers with greater self-confidence. The results of this Teaching Assistance activity include the MBKM report and the 2023 Serina VII Registration Form.